2016
DOI: 10.1210/en.2015-2057
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nicotinic Acetylcholine Receptors Decreases Apoptosis in Human and Female Murine Pancreatic Islets

Abstract: Type 1 diabetes (T1DM) results from destruction of most insulin-secreting pancreatic ␤-cells. The persistence of ␤-cells decades after the onset of the disease indicates that the resistance of individual cells to the autoimmune insult is heterogeneous and might depend on the metabolic status of a cell at a given moment. The aim of this study is to investigate whether activation of nicotinic acetylcholine receptors (nACh-Rs) could increase ␤-cell resistance against the adverse environment prevailing at the onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
4
1
Order By: Relevance
“…These data support the hypothesis that ␣7R agonist treatment, in the context of MLDS-induced islet inflammation, preserves BCM by reducing proinflammatory drive and enhancing survival. Our results are also in accord with a recent study demonstrating that nonspecific nAChR activation attenuates inflammatory cytokine-mediated ␤-cell apoptosis in mouse and human islets by reducing endoplasmic reticulum stress and alleviating the mitochondrial/Bcl2 protein-driven apoptotic cascade (41).…”
Section: Discussionsupporting
confidence: 93%
“…These data support the hypothesis that ␣7R agonist treatment, in the context of MLDS-induced islet inflammation, preserves BCM by reducing proinflammatory drive and enhancing survival. Our results are also in accord with a recent study demonstrating that nonspecific nAChR activation attenuates inflammatory cytokine-mediated ␤-cell apoptosis in mouse and human islets by reducing endoplasmic reticulum stress and alleviating the mitochondrial/Bcl2 protein-driven apoptotic cascade (41).…”
Section: Discussionsupporting
confidence: 93%
“…55 Similarly, VN could exert anti-inflammatory effects on pancreatic islets via Ach and the subsequent activation of α7nAChR (alpha-7 nicotinic acetylcholine receptor). 56 In contrast, in the present study, we found a striking loss of IL-1β immunostaining in β cells from vagotomized rats, a response also observed in splenectomized rats. These data suggest that, at in least in healthy conditions, the VN could modulate IL-1β production in β cells with splenic participation.…”
Section: Discussioncontrasting
confidence: 99%
“…To investigate nAChR signaling in detail, we focused on signaling through the α7 subunit for the following reasons. First, it is the most commonly expressed subunit among the nAChR subunits in rodent β‐cells. Second, the mechanisms underlying the recently revealed anti‐apoptotic effects of a complete and highly specific nAChR α7 agonist, PNU, in β‐cells are still unknown.…”
Section: Resultsmentioning
confidence: 99%